Analisis Tingkat Efisiensi Daya dan Biaya Penggunaan Lampu Neon Sistem Elektronik Terhadap Neon Sistem Trafo Berdasarkan Desain Eksperimen Faktorial - Rr. Dhiasty Mahayanti; Bambang Suhardi; Rahmaniyah Dwi Astuti (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2004)
New innovation of electrics technology is not basically easy to permeated by society, includingsaving energy lamp. In fact, theese topics is interesting for the researchers. Reducing of electrics consumption in usage of lamp almost 50% from total cost usage of electrics energy. This research aim to choose the best tube lamp by considering of energy efficiency and reduce expense of electrics. Measuring input energy and output energy is conducted to two lamp type taken as this research namely transformer system lamp (NST) and electronic system lamp(NSE).Measuring of input energy and output energy is conduted by two factors experimental design with one block (Factorial Experiment Randomized Block Design). Theese factors are tube type and ballast type, while energy size as block. Result of research is analysed by using analysis of variant (Anova). Calculation of usage expense is conducted by considering four category according to electrics basic tariff (TDL). Based on analysis of variant, it is known that tube type and factor interaction do not have an effect significantly to input energy and output energy. While for the efficiency of energy, only tube type factor which do not show influence significantly.Percentage differenciation average of input energy, output energy, and energy efficiency NSE each 49%, 63%, and 49% bigger than NST. NSE more beneficial than NST as technically and economically. Most economical NSE is 20 watt.